Pemilu Legislatif Sebagai Media Pendidikan Politik Kewarganegaraan Siswa Sekolah Dasar - Sigit Waluyo (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2007)
Abstract: Political education should be socialized to elementary schools’ students. One of the appropriate media is using general election process context. General election is one of political activities that can be observed and analysed by elementary schools’ students. By analyzing general election process, students will have direct experience in effort to studying the meaning of democracy. In conclusion, the general election process can be seen as a meaningful political learning media for elementary schools’ students.